Water Quality Study at the Downstream of Gunung Belumut - Haniffa, Mohammad Hafiz; Ahmad Nazri, Mohd Ariff (Recent Trends in Civil Engineering and Built Environment, 2023)
Sungai Dengar is located at the downstream of Gunung Belumut. The surrounding at the downstream was mainly used for agriculture purpose. A study was taken at this river to analysis the water quality of the downstream that is located at Sungai Dengar, based on the parameter of water quality which are DO, BOD, COD, pH, TSS and AN, in order to classify the river water based on WQI-DOE. The objective of this study is to determine the water quality at the downstream of Gunung Belumut and to identify the relationship of the downstream of Gunung Belumut with its surrounding land use. There was 3 sampling station of different location that have been selected to obtain the water sample along Sungai Dengar. In order to control variables that might affect the result, all the parameters was analyzed in laboratory which produce the average from three stations are, value of DO is 7.91, BOD is 482, COD is 28.31, pH is 6.92, TSS is 115.3 and AN is 1.72. In that case, that the water has been classified as class III where it is slightly polluted. The surrounding land used is a major factor that influencing the current water quality at the downstream of Gunung Belumut. By completing this study, the current water quality at the downstream of Gunung Belumut has been analyzed and all the precautions can be taken, in order to prevent the river from continuously being polluted in the future.